Intimacy or Alienation: Revisiting Sibling Relationships from the Perspective of Preschoolers - Yao, Peiling; Song, Yue (Advances in Social Sciences Research Journal, 2025)
This study aims to revisit sibling relationships and trace the contours of current sibling interactions in Chinese preschoolers from children's perspective since sibling relationships have long been absent in traditional Chinese culture since the 1980s. Forty-one 3- to 6-year-olds (mean age = 48.12 months, sd age =0.50 months, 17 boys) from two-child families participated in this study. Semi-structured interviews and thematic drawings were used to measure children's daily interactions with their siblings. Results found that there are different types of prosocial behaviors among siblings. Prosocial behaviors are affected by gender and gender combinations, not by age. There is a correlation between children's representations and drawings. These results indicate the positive prosocial behaviors among siblings in most Chinese preschoolers. These findings contribute to revisiting of the sibling relationships of Chinese preschoolers in the context of a new policy and also extend the knowledge of sibling prosocial interactions from children's perspectives.